MENINGKATKAN PRESTASI BELAJAR MATEMATIKA MELALUI ALAT PERAGA KERTAS LIPAT TENTANG MENGENAL ARTI PECAHAN PADA SISWA KELAS IV SDN 012 RAMBAH HLIR KABUPATEN ROKAN HULU - Dahlia Dahlia (JURNAL PENDIDIKAN ROKANIA, 2020)
This study is entitled "Efforts to Improve Learning Outcomesin Grade IV Students of SDN 012 Rambah Hilir". on learningmathematics about recognizing the meaning of fractions byusing paper folding props. with folding paper ribs obtainedstudent learning outcomes are increasing and meet theminimum completeness criteria that have been determined.Teaching aids used by each teacher are diverse, one of whichis a teaching aid used to increase and enhance studentlearning achievement. Classroom Action Research (CAR) isdivided into two cycles using the Classroom Action Research(CAR) design which is divided into two cycles. Each cycleconsists of 4 (four) stages, namely: (1) Improvement Plan, (2)Improvement Implementation, (3) Data Collection, (4)Reflection. The study was conducted at SDN 012 in RambahHilir District, Rokan Hulu Regency, with the number ofGrade IV students totaling 20 students consisting of 8 malestudents and 12 female students. The results of the studybefore the cycle showed that students still did not master thematerial, especially in determining the meaning of fractions,in the process of getting 40% completeness while in the firstcycle 60% completeness results, in the second cycle reached95% completeness proved that after using folding paperprops students are active in teaching and learning activities.From the results of this research it seems clear that usingpaper folding props can improve student achievement inlearning Mathematics Students of SDN 012 Rambah Hilir,especially in identifying the meaning of fractions.